answer:
sum: 19 + 7 = 26
difference: 19 - 7 = 12
Explanation:
the sum of x and y is 26. in other words, x plus y equals 26 and can be written as equation a:
x + y = 26
the difference between x and y is 12. in other words, x minus y equals 12 and can be written as equation b:
x - y = 12
now solve equation b for x to get the revised equation b:
x - y = 12
x = 12 + y
then substitute x in equation a from the revised equation b and then solve for y:
x + y = 26
12 + y + y = 26
12 + 2y = 26
2y = 14
y = 7
now we know y is 7. this means that we can substitute y for 7 in equation a and solve for x:
x + y = 26
x + 7 = 26
X = 19
good luck :)
hopefully, this helps
have a great day !!